Tribute. MLO thanks... (Medical Laboratory Observer (MLO), 2007)
In conjunction with April's weeklong celebration of National Medical Laboratory Professionals Week, April 22-28, MLO throws the spotlight on its cadre of contributors, some of whom have been with us since the beginning.